Maternal and perinatal outcomes of pre-referral magnesium sulfate treatment in severe preeclampsia patients - Rizki Amalia Sari; Sulistiawati Sulistiawati; Ernawati Ernawati (Majalah Obstetri dan Ginekologi, 2022)
HIGHLIGHTS 1. Consumption of magnesium sulfate is recommended for prevention against eclampsia. 2. Magnesium sulfate administration to preeclamptic mothers is effective in reducing the risk of eclampsia.3. Pre-referral magnesium sulfate administration and maternal and perinatal outcomes in severe preeclampsia patients was analyzed.4. Magnesium sulfate did reduce eclampsia risk, but not ICU and NICU care rates, maternal mortality, perinatal asphyxia, and perinatal mortality.   ABSTRACT Objectives: This study analyzed the association between pre- referral magnesium sulfate administration and maternal and perinatal outcomes in severe preeclampsia patients. Materials and Methods: This was a retrospective observational analytic study using cross-sectional design. Samples were 132 pregnant women with preeclampsia referred to dr. Saiful Anwar, Hospital Malang, Indonesia in 2019. Data were taken from the patients’ medical records. Maternal outcomes measured in this study were the incidence of eclampsia, ICU care, and maternal mortality, while the perinatal outcomes included the incidence of asphyxia, NICU care, and perinatal mortality. Results: Patients’ history of magnesium sulphate administration significantly associated with the incidence of eclampsia with p-value 0.035 and odds ratio (OR) 2.413, thus consumption of magnesium sulphate could reduce the risk of seizures. However, it did not associate with either maternal ICU care outcomes (p-value 0.087, OR 2.028), or maternal mortality (p-value 0.573). No relationship was found neither between history of magnesium sulphate administration in pregnant women with severe preeclampsia and perinatal outcomes nor with the incidence of asphyxia (p-value 0. 577, OR 0.795), with NICU treatment (p-value 0.205, OR 0.579), and with perinatal mortality (p-value 0.153, OR 3.259). Conclusion: Magnesium sulfate reduced the risk of eclampsia, yet it did not affect either the rate of ICU care, maternal mortality, incidence rate of perinatal asphyxia, the rate of NICU care, or perinatal mortality.